The origins of magnetic anomaly lows associated with three impact structures. - Scott, Ronald Glenn. (University of Ottawa (Canada), 1996)
Drill cores from three Canadian impact structures were analysed for rock magnetic properties and mineralogy, in order to explain the reduced magnetizations associated with these structures. Samples from the drill cores were cut and measured for AMS and NRM parameters. Drill cores from the twin impact craters of the Clearwater structure exhibited different natural remanent magnetization (NRM) characteristics and samples from their respective drill cores were subject to demagnetization by alternating field and thermal techniques. The difference noted in their NRM characteristics was attributed to the acquisition of a viscous remanent magnetization (VRM) at depth in Clearwater East. Both magnetic susceptibilities and remanent magnetizations are well below regional values in impact generated breccias, melt rocks, shocked crystalline rocks, and in post-impact sedimentary infill. The processes of brecciation, alteration, shock, and infill by non-magnetic sediments contribute to the development of the magnetic lows. However, a significant component of the magnetic anomalies was found by forward modeling to derive from the unshocked basement rocks beneath the impact structures. This zone of reduced magnetization may be caused by the partial demagnetization of magnetite by the impact-induced transient stress wave travelling away from the point of impact, and the possible acquisition of a lower intensity shock remanent magnetization in the target rocks at depth. (Abstract shortened by UMI.)
Keywords: Geophysics.